Adherence clubs for long‐term provision of antiretroviral therapy: cost‐effectiveness and access analysis from Khayelitsha, South Africa. Issue 9 (10th July 2016) - Bango, Funeka; Ashmore, John; Wilkinson, Lynne; van Cutsem, Gilles; Cleary, Susan
Abstract: Objectives: As the scale of the South African HIV epidemic calls for innovative models of care that improve accessibility for patients while overcoming chronic human resource shortages, we (i) assess the cost‐effectiveness of lay health worker‐led group adherence clubs, in comparison with a nurse‐driven 'standard of care' and (ii) describe and evaluate the associated patient cost and accessibility differences. Methods: Our cost‐effectiveness analysis compares an 'adherence club' innovation to conventional nurse‐driven care within a busy primary healthcare setting in Khayelitsha, South Africa. In each alternative, we calculate provider costs and estimate rates of retention in care and viral suppression as key measures of programme effectiveness. All results are presented on an annual or per patient‐year basis. In the same setting, a smaller sample of patients was interviewed to understand the direct and indirect non‐healthcare cost and access implications of the alternatives. Access was measured using McIntyre and colleagues' 2009 framework. Results: Adherence clubs were the more cost‐effective model of care, with a cost per patient‐year of $300 vs . $374 and retention in care at 1 year of 98.03% (95% CI 97.67–98.33) for clubs vs . 95.49% (95% CI 95.01–95.94) for standard of care. Viral suppression in clubs was 99.06% (95% CI 98.82–99.27) for clubs vs . 97.20% (95% CI 96.81–97.56) for standard of care. When interviewed, club patients reported fewer missed visits, shorter waiting times and higher acceptability of services compared to standard of care. Conclusions: Adherence clubs offer the potential to enhance healthcare efficiency and patient accessibility. Their scale‐up should be supported.